Optimalisasi RKAS Dalam Meningkatkan Mutu Sekolah Melalui Pengembangan Human Capital Di SMKN 3 Tuban - Sofi Yulia Rakhmawati (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to identify how the development of human capital can be improved through optimizing the School Activity Plan and Budget (RKAS) in an effort to improve school quality. Through a qualitative approach, data was collected through observation, interviews, and analysis of documents related to the implementation of the RKAS at SMKN 3 Tuban. The results of the research show that developing human capital through optimizing RKAS has the potential to improve school quality. Funds allocated wisely for teacher and student training programs, as well as extracurricular support and collaboration with other schools and industry visits, were able to develop teacher and student competencies. Optimal implementation of RKAS plays an important role in facilitating human capital development by ensuring proper allocation of funds and programs that are relevant to school needs.